2016
DOI: 10.1016/j.spmi.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth temperature of seed layer on the structural and optical properties of ZnO nanorods

Abstract: The structural and optical properties of ZnO nanorods are investigated as a function of growth temperature of the seed layer. The seed layer comprising of ZnO nanocrystallites is grown on ITO substrates at five different temperatures (150-550 °C) and the nanorods are grown on the seed layer by the facile hydrothermal method. The seed layer grown at 350 ºC is observed to be uniformly textured with c-axis orientation leading to the synthesis of vertically aligned nanorods with smaller diameter. The HR-TEM analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Therefore, the replacement of TiO 2 with a one-dimensional nanometer ZnO array significantly improves the electron transfer efficiency. The ZnO one-dimensional nanorod arrays are superior to ZnO thin films in terms of optical properties and fast electron transport properties [10][11][12]. When n-type ZnO is combined with a P-type semiconductor, ZnO enhances the visible light absorption as an anti-reflection photon window and also serves as an n-type semiconductor material that generates carriers and provides a depletion layer [13,14] and a built-in electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the replacement of TiO 2 with a one-dimensional nanometer ZnO array significantly improves the electron transfer efficiency. The ZnO one-dimensional nanorod arrays are superior to ZnO thin films in terms of optical properties and fast electron transport properties [10][11][12]. When n-type ZnO is combined with a P-type semiconductor, ZnO enhances the visible light absorption as an anti-reflection photon window and also serves as an n-type semiconductor material that generates carriers and provides a depletion layer [13,14] and a built-in electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the types of seed layer that used either monoethanolamine (MEA) or potassium hydroxide (KOH), and their effects on the resulting ZnO NRs, were compared and analyzed by Kashif et al [28]. Another method to optimize the ZnO NR's properties was by the preheating treatment for the seed layer [29][30][31][32]. Dou et al reported another way to increase photovoltaic performance of ZnO NR-based DSC, by using a Ga-doped seed layer [33].…”
Section: Introductionmentioning
confidence: 99%
“…The high intensity and narrow thickness of the peaks, mainly in relation to the planes (100), (002) and (101) in the XRD indicate a polycrystalline structural characteristic of the ZnO nanoparticles powder. 37 From the XRD pattern it is evident the absence of peaks that do not belong to the wurtzite phase, this demonstrates that precipitation synthesis formed ZnO nanoparticles without other structures that differ from the ZnO wurtzite hexagon. Moreover, the excess of ions (OH À ) at pH between 10 and 11 can generate the formation of ZnO in zinc hydroxide however, the hydrogen potential measurement of the ZnOQD colloid resulted in pH 9.4, which corroborates the presence of an only phase on XRD.…”
Section: Photocatalytic Assaymentioning
confidence: 97%